2016
DOI: 10.15366/rimcafd2016.62.008
|View full text |Cite
|
Sign up to set email alerts
|

La precisión del movimiento imaginado y la recepción de balón en niños / The Accuracy of the Motor Imagery and the Ball Reception in Children

Abstract: RESUMENEstudios recientes observaron que las imágenes motrices se desarrollan de forma entrelazada con el desarrollo de las habilidades motrices en niños. La finalidad de este estudio es analizar en qué medida la imagen motriz de los elementos necesarios para resolver un problema motor (la recepción de un balón), se relaciona con los niveles de habilidad en niños (3 -9 años). La muestra estuvo formada por 215 participantes (87 chicos y 118 chicas), (M = 5,94, DT = 1,47). Se ha utilizado una metodología mixta:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…The more difficult the posture, the greater the cognitive load and the stronger the corresponding PFC activation. Cecchini et al (2016) found that motor imagery is developed linked to the development of motor skills. Therefore, enhanced activation in the PFC during actual performance of postures may be a reasonable interpretation for efficient neural recruitment during the mental imagery of postures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more difficult the posture, the greater the cognitive load and the stronger the corresponding PFC activation. Cecchini et al (2016) found that motor imagery is developed linked to the development of motor skills. Therefore, enhanced activation in the PFC during actual performance of postures may be a reasonable interpretation for efficient neural recruitment during the mental imagery of postures.…”
Section: Discussionmentioning
confidence: 99%
“…The more difficult the posture, the greater the cognitive load and the stronger the corresponding PFC activation. Cecchini al. (2016) found that motor imagery is developed linked to the development of motor skills.…”
Section: Mental Imagery Of Yoga Posturesmentioning
confidence: 99%
“…Este trabajo establecerá mejoras en todas las esferas de su desarrollo y servirá de base para aprendizajes superiores. En este bloque se podrán trabajar reptaciones, manipulaciones de objetos y móviles, gateo, saltos, lanzamientos, giros, volteos, trepa, suspensiones, marcha, carrera… (Cechini-Estrada, Fernández-Losa & Pallasá-Manteca, 2016;Andrés, 2014;Zubiaur-González, 2005). Pero también está contemplada aquí la iniciación a las habilidades gimnásticas, como la rueda lateral, el equilibrio invertido de brazos, voltereta atrás o adelante, entre otras.…”
Section: Sobre Los Contenidos a Enseñarunclassified